(untitled) (UNIZIK Journal of STM Education, 2024)
Remediation of common process errors committed by senior secondary three (SS3) students in geometry was investigated. Four research questions and three null hypotheses tested at .05 alpha level guided the study. A mixed design involving the descriptive survey, instrumentation and quasiexperimental designs was used. A sample of 297 and 144 SS3 students for initial identification and final treatment with developed package respectively participated in the study. The sample was drawn from a population of 6,265 SS3 students from coeducational secondary schools in Awka Education Zone, Anambra State using multistage sampling procedure. The Mathematics Diagnostic Test (MDT) and Mathematics Remediation Package (MRP) were used as instrument for data collection and instructional tools respectively which were validated by three experts. The reliability of MDT was determined using interrater method. The scores obtained from five independent raters were analysed using Kendalls coefficient of concordance (W) which yielded reliability index of .88. The MDT was used to identify the common process errors committed by students before and after the treatment with MRP. Data obtained were analysed using frequency, percentage, Mann Whitney U test and Wilcoxon signed rank test. The findings revealed among others that five (5) common process errors identified were factual (42.7%), accuracy (23%), diagrammatic (15%), blunder (10.9%) and algorithm (8.4%); the use of MRP was effective in reducing the errors committed by the students and the developed remediation package was gender friendly. Based on the findings, it was recommended that Mathematics teachers should use MDT to identify students’ common process errors in Geometry and MRP to reduce the incidence of common process errors in the subject for improved performance in internal and external examinations.